The effectiveness of repetitive transcranial magnetic stimulation (rTMS) in patients with catatonia associated with another mental disorder: A systematic review - Sarvenaz Esmaeelzadeh (21976673) (2024)
Background Catatonia is a rare but life-threatening condition characterized by a constellation of psychomotor disturbances. The most widely used treatments of catatonia include benzodiazepines and electroconvulsive therapy. Despite the widespread use of benzodiazepines and the high response rate of catatonia to ECT, there are instances where catatonia does not respond to first-line treatments. This study aimed to evaluate the efficacy of repetitive transcranial magnetic stimulation (rTMS) in managing catatonia. Methods A systematic literature search was conducted on the following databases: Medline, PubMed, Cochrane Library, Embase, PsycINFO and ClinicalTrials.gov for registered but not yet published studies. Results Out of 244 initially identified articles, there remained eight case reports and 1 case series eligible after screening. Of the twelve total cases, nine showed clinical improvement. However, there was significant heterogeneity in the complexity of the clinical situation, the severity of clinical features of catatonia, underlying causes, and rTMS treatment protocols between studies. Conclusion The results of this study are inconclusive. However, rTMS might be trialed for the management of catatonia when first-line treatment options fail, are unavailable, or need to be used with caution. Our review incorporating the most up to date evidence highlights the need for more extensive, standardized, randomized clinical trials to investigate the efficacy of rTMS for treating catatonia. Other Information Published in: Asian Journal of Psychiatry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ajp.2024.104311